Approximation by Some Singular Operators Type of Functions from a Generalized Zygmund Space - Krasniqi, Xhevat; Mohapatra, Ram (Armenian Journal of Mathematics, 2025)
This study continues previous research on the approximation of functions by means of singular integrals. We begin by introducing the truncated Picard singular integral. Subsequently, using this integral along with the classical Picard--Cauchy and Gauss--Weierstrass singular integrals, we establish the orders of approximation for functions belonging to a generalized Zygmund space, both in the $L^p$-norm and in the corresponding norm of the generalized Zygmund space.